Training on Teaching English based on Kurikulum Merdeka for Elementary School Teachers - Syarifah, Eva Fitriani; Nurhidayat, Eka (International Journal of Public Devotion, 2024)
In Kurikulum Merdeka, English becomes one of the compulsory subjects at elementary school level after being abolished in the previous curriculum. This is a challenge in itself for teachers in elementary schools. This is because English subjects in elementary schools are usually taught by each class teacher. Based on the results of observations in three elementary schools in Sukahaji District, Majalengka Regency, class teachers experienced difficulties in delivering English materials to students. Therefore, this service community aims to provide English language learning training based on the Kurikulum Merdeka. The targets of this service activity are elementary school teachers in Sukahaji District, Majalengka Regency. This training was carried out through focus group discussions regarding English language learning models for young learners based on Kurikulum Merdeka, textbook reviews, and basic skills training related to pronunciation, vocabulary, and grammar. At the end of the activity, teachers were grouped and asked to prepare teaching modules that were relevant to Kurikulum Merdeka. Based on the design of the teaching modules prepared after this training activity, the learning models used are more varied, such as the use of discovery learning models, project-based learning, problem-based learning, and inquiry learning. Apart from that, the existence of additional references apart from application-based or web-based textbooks is an added value regarding the digital literacy possessed by teachers.